PEMANFAATAN CANGKANG BEKICOT MENJADI KETERAMPILAN GANTUNGAN KUNCI DI DESA BOGAK BESAR KABUPATEN SERDANG BEDAGAI - serahayati hasibuan; Surianti (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Snail shells carried by ocean currents to the shore can be reused into various types of skills. The basic shape and color of the snail shell add to its aesthetic value if it is processed into various skills, one of which is making it a keychain. This empowerment activity aims to preserve coastal areas from snail shell waste. The method used by the author includes providing material about opportunities and utilization of natural products, namely snail shell waste, then this activity also carries out manufacturing practices, as well as discussions. The results of the empowerment efforts show that most of the participants are not aware of the existence of business opportunities by utilizing natural products. After conducting a discussion among the participants, they intended to make hand skills using natural products around the beach.